Effect of low‐intensity, low‐frequency ultrasound treatment on anthropometry, subcutaneous adipose tissue, and body composition of young normal weight females. (September 2014) - Milanese, Chiara; Cavedon, Valentina; Piscitelli, Francesco; Zancanaro, Carlo
Summary Background Low‐intensity, low‐frequency ultrasound is increasingly being used for noninvasive, external body contouring as an alternative to liposuction or laser treatments. Objectives To evaluate the effect of chronic localized treatment with a novel ultrasound device on subcutaneous adipose tissue thickness and fat mass in young, normal weight women. Methods Twenty‐eight females (mean age = 25.5 ± 0.66 [SE] year, mean BMI = 22.1 ± 0.37 kg/m2) underwent a 10‐week bilateral treatment with the device in the gluteus–buttock–thigh area (Lipolysis program: ultrasound frequency = 150 kHz; power = 1.65 W/cm2), 48 min per session, two sessions a week. Subcutaneous adipose tissue thickness and fat mass were evaluated before and after treatment with ultrasound and dual‐energy X‐ray absorptiometry, respectively. Results Treatment was well tolerated by all participants. At the end of treatment, statistically significant reduction of subcutaneous adipose tissue thickness was found bilaterally at the gluteus and thigh site (−2.03 ÷ −2.79%). Trunk and lower limb fat mass were reduced as well (−3.48 ÷ −3.97%). Conclusions A 10‐week, low‐intensity, low‐frequency localized external ultrasound treatment is effective in reducing adipose tissue in females.